Ultrasonic Membrane Anaerobic System (UMAS) Applications Intreating Slaughterhouse Wastewater - Nour, A. H.; R. M., Yunus; Azhari, H. Nour (AENSI Publishing, 2015)
In the wake of energy crisis and the drive to reduce CO2 emissions, the alternative energy sources are much demanded in order to reduce energy consumption, to meet legal requirements on emissions, and for cost reduction and increased quality. The direct discharge of slaughterhouse wastewater causes serious environmental pollution due to its high chemical oxygen demand (COD), Total suspended solids (TSS) and biochemical oxygen demand (BOD). The traditional methods for treating slaughterhouse wastewater have two undesired aspects which areeconomic and environmental. Therefore, as alternative, ultrasonic membrane anaerobic system (UMAS) was used, as cost effective method for treating slaughterhouse wastewater.Experimentsresults have shown that the mixed liquor volatile suspended solids (MLSS) concentration ranges from7,800 to 13,620 mg/l while mixed liquor volatile suspended solids (MLVSS) rangeswas 5,359 to 11,424 mg/l. Three kinetic models were used to fit the kinetic models of slaughterhouse treatment at organic loading rates ranging from 3 to 11 kg COD/m3/d. UMAS performance has shown the COD removal efficiencywas from 94.8 to 96.5% with hydraulic retention time, HRT from 308.6 to 8.7 days. The coefficient of growth yield, Y was found to be 0.52gVSS/g COD the specific microorganism decay rate was 0.21 d-1 and the methane gas yield production rate was between 0.24 l/g COD/d and 0.56 l/g COD/d.